UV-curable Schiff base-containing polymeric adsorbent for selective and efficient removal of Au(III) from aqueous solutions - AYDIN URUCU, OYA (My University, 2023)
UV-curable polymeric adsorbent was prepared using a diacrylate-functionalized hydrazone-oxime monomer (DAFHOM), trimethylolpropane triacrylate (TMPTA), and trimethylolpropane tris(3-mercaptopropionate) (TMPTP) through UV-initiated thiol-ene click reaction. Initially, a novel hydrazone-oxime-based Schiff base ligand was synthesized and modified with diacrylate functionality to prepare the UV-curable polymeric adsorbent. The structures of DAFHOM and the resulting polymeric adsorbent were confirmed using Fourier Transform Infrared Spectroscopy (FTIR) analysis. Additionally, the thermal behavior of the UV-cured adsorbent was investigated through thermal gravimetric analysis (TGA), which revealed that the adsorbent exhibited good stability and did not degrade at room temperature. The adsorption performance of the UV-curable polymeric adsorbent for Au(III) from aqueous solutions was studied under various experimental conditions, including pH, contact time, and initial metal concentration. The UV-curable polymeric adsorbent demonstrated effective and selective Au(III) adsorption from aqueous solutions. The findings indicated that removing Au(III) from water solutions positively correlated with pH, particularly within the pH range of 0.5–2.5. However, the efficiency declined when the pH exceeded 1.5. Among the various adsorption isotherm models investigated, the Langmuir model was found to be the most suitable for describing the behavior of the adsorbent. The maximum adsorption capacity of the adsorbent for Au(III) was determined to be 30.06 mg/g. In batch experiments, the UV-curable adsorbent displayed promising selectivity towards Au(III), even in the presence of competitive ions such as Cu(II), Pb(II), and Cd(II).
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, KOMPOZİTLER; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, COMPOSITES; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Malzeme Bilimi; Fizik Bilimleri; Malzemelerin mekaniği; Malzeme Kimyası; General Materials Science; Physical Sciences; Mechanics of Materials; Materials Chemistry; Au(III) adsorption; Hydrazone-oxime monomer; Schiff base; Thiol–ene click reaction